Optimization of genomic DNA shearing by sonication for next-generation sequencing library preparation - Lee, Le Jie; Abdullah, Maha (Malaysian Society for Molecular Biology and Biotechnology, 2014)
Next-generation sequencing (NGS) technologies, capable of sequencing genomic DNA and RNA at high throughput with unprecedented speed, have revolutionized genomic research as well as clinical diagnosis. DNA fragmentation is a critical step in library preparation in all NGS platforms, and determines the quality and diversity of the final library. DNA shearing by acoustic sonication is one of the ways to randomly break DNA into small fragments, however many variables affect the outcome. Here, we describe an optimized procedure to shear genomic DNA into fragments of 150 bp to 120 bp using a focused-ultrasonicator. Parameters that were assessed included DNA quantity, the effect of repeat shearing, treatment time, peak incident power and shearing reproducibility. This input of pure and optimum quality DNA samples is an essential starting point to the NGS system. We identified peak incident power as being the key determining factor in obtaining small target fragments. By increasing the peak incident power to 75W, a peak size within the 150 bp to 200 bp range was achievable, a result which was reproducible in multiple samples. Repeat shearing and increased treatment time were less successful in producing optimally sized DNA fragments. The proposed method may be used as a guide for NGS users involved in library construction, particularly when small fragment sizes are required.